MAFHŪM I ̔TIBĀR AL-MA ̔ĀL WA TAṬBȊQUHŪ FȊ SŪRAH AL-NISĀ’: Dirāsah Waṣfiyyah liāyāt al-Mujtama ̔ - Mokhammad Ali Ridlo (STAI AL-ANWAR SARANG, 2020)
One of the efforts to maintain the law of siyāq (context) is by applying the concept of i'tibār al-maāl to naṣ texts (al-Qur`an and Hadith). It is because the text is general understanding while the law is static, so if the law is applied, it will not regard at a person's condition and context, nor will it even see the effect of the law and its origin. Such law is not allowed in Islamic law which prohibits the application of law regardless of the context of the incident and the application of the law. Therefore, this discussion comes with a qualitative-descriptive method to analyze the concept of i'tibār al-ma’āl and its application in surah al-Nisa' especially in social verses. This concept is part of Imam Malik's method of exploring law, and it seems tobe lack of discussion or reference in Indonesian, even the Arabic references are also rarely. On the other hand, surah al-Nisa is one of the long chapters and discusses a lot about social society, for example about how to build a good family strategy to build a good society.